Audit Energi Dan Analisa Penghematan Energi Pada Pulp Machine 1 Dan 2 PT. Riau Andalan Pulp Dan Paper - Samsu Rizal; Zulfansyah Zulfansyah; Hari Rionaldo; Sri Wahdini Rahmi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Energy auditing is one of the steps made in an effort to realize energy saving programs. The energy widely used in the pulp and paper industries is thermal energy (steam) and electrical energy. Pulp drying is one of the processes that many use such energy. The thermal energy used was of low to medium pressurized steam, which used to increase air temperature to dry pulp sheet. Research were conducted to identified energy usage and potency of energy saving in pulp machine especially in Pulp machine 1 and 2 area. The results of the study were found the influence of downtime to production cost. 30 minutes down time will increase production cost to 0.3545/ton pulp. Used of acacia as raw material will make pulp machine possible to run 1 screening system. It give benefit 2180.8 per day. Besides, the study also found four “steam trap” units and six “valve” units with “Passing